Periostin-integrin signaling in hepatocellular carcinoma: from biological function to clinical application - Lei, Jun; Liu, Yong; Yuan, Shuai; Yuan, Xiaxia; Yuan, Qi (Frontiers in Cell and Developmental Biology, 2025)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer death worldwide and the most common primary tumor. Periostin (POSTN) is located in the extracellular matrix (ECM) and triggers tumor growth signals by binding to integrin receptors. The interaction of highly expressed POSTN with cell surface receptor integrins regulates intracellular signaling pathways and promotes HCC progression. In this review, the structure and isoforms of POSTN will be summarized, and the relationship between POSTN-integrin signaling and the diagnosis and prognosis of HCC patients, tumor cell proliferation and metastasis, immune escape, cancer stem cells and angiogenesis will be reviewed. The interaction between POSTN-integrin and the key signaling pathways of HCC and its mechanism in disease progression were emphasized, and the potential value of this signaling axis as a therapeutic target for HCC was explored, providing a theoretical basis for in-depth understanding of the pathophysiological process of HCC and the development of new therapeutic strategies.